2022
DOI: 10.1038/s41467-022-31555-2
|View full text |Cite
|
Sign up to set email alerts
|

A natural uORF variant confers phosphorus acquisition diversity in soybean

Abstract: Phosphorus (P) is an essential element for all organisms. Because P fertilizers are a non-renewable resource and high fixation in soils, sustainable agriculture requires researchers to improve crop P acquisition efficiency. Here, we report a strong association signal at a locus of CPU1 (component of phosphorus uptake 1), from a genome-wide association study of P acquisition efficiency in a soybean core collection grown in the field. A SEC12-like gene, GmPHF1, is identified as the causal gene for CPU1. GmPHF1 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 71 publications
2
46
0
Order By: Relevance
“…For example, alleles as natural allelic variation in haplotypes of GmINS1 and the P efficiency locus 1 could be the targets for breeding varieties with improvements in P efficiency and N fixation efficiency (Li et al ., 2018; Yang et al ., 2019). Recently, a natural uORF variant has been identified in the promoter region of GmPHF1 , which further confers higher translation efficiency of GmPTF1 protein and finally controls the polar localization of GmPT4 to the plasma membrane of root epidermal cells, and thus enhancing P acquisition efficiency (Guo et al ., 2022).…”
Section: Strategies To Improve P Use Efficiencies For High Snf In Leg...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, alleles as natural allelic variation in haplotypes of GmINS1 and the P efficiency locus 1 could be the targets for breeding varieties with improvements in P efficiency and N fixation efficiency (Li et al ., 2018; Yang et al ., 2019). Recently, a natural uORF variant has been identified in the promoter region of GmPHF1 , which further confers higher translation efficiency of GmPTF1 protein and finally controls the polar localization of GmPT4 to the plasma membrane of root epidermal cells, and thus enhancing P acquisition efficiency (Guo et al ., 2022).…”
Section: Strategies To Improve P Use Efficiencies For High Snf In Leg...mentioning
confidence: 99%
“…Amon them, GmPT1 , GmPT4 , GmPT10 , GmPT12 , and GmPT13 showed high expressional levels in roots and have been implicated in P uptake by roots (Qin et al ., 2012a; Fan et al ., 2013). GmPT4 is localized on the root epidermal cells of soybean and contributes to the P uptake by roots (Guo et al ., 2022). On the contrary, some P transporters such as GmPT5 and GmPT10 are reported to be involved in P translocation from host roots to nodules in soybean (Qin et al ., 2012b; Lu et al ., 2020; Fig.…”
Section: Allocation Of P For Symbiotic N Fixationmentioning
confidence: 99%
“…Some studies have suggested that loss of uORF function is associated with human disease ( 8 , 9 ). Studies in plants have found that the uORFs are associated with disease resistance, nutrient absorption and other traits ( 7 , 10 , 11 ). Due to the importance and widespread occurrence of uORFs, many studies have investigated the utilization of uORFs to manipulate translation and phenotypes ( 12–14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since symbiotic N fixation (SNF) in nodules requires significant inputs of energy, legumes are generally considered to have a high P requirement (Sulieman and Tran, 2015;Pang et al, 2018b;Zhong et al, 2023). Furthermore, as N-fixing root nodules are strong P sinks, the growth and yield of legumes are dramatically decreased by 30-40% under low P stress (Tesfaye et al, 2007;Valdeś-Loṕez and Hernańdez, 2008;Chen et al, 2011;Qin et al, 2012;Guo et al, 2022). Thus, low P availability is regarded as an important constraint for legume production.…”
Section: Introductionmentioning
confidence: 99%